Is Preoperative Duration of Symptoms a Significant Predictor of Functional Status and Quality of Life Outcomes in Patients Undergoing Surgery for the Treatment of Degenerative Cervical Myelopathy?. Issue 1 (April 2016) - Tetreault, Lindsay; Kopjar, Branko; Wilson, Jefferson; Arnold, Paul; Fehlings, Michael
Introduction: Longstanding compression of the spinal cord in patients with degenerative cervical myelopathy (DCM) may result in irreversible neural tissue damage. This study aims to analyze whether a longer duration of symptoms is associated with poor surgical outcomes and to determine the optimal timing for decompressive surgery. Material and Methods: Three hundred and fifty patients with symptomatic DCM were prospectively enrolled in either the CSM-North America or International study at 12 sites in North America. For each patient, extensive demographic information was collected, including age, co-morbidities, and a self-reported estimate of preoperative duration of symptoms. Postoperative functional status and quality of life were evaluated at 6-, 12- and 24-months using the modified Japanese Orthopaedic Association (mJOA), Nurick grade, Neck Disability Index (NDI) and Short-Form-36 (SF-36) Physical (PCS) and Mental (MCS) Component Scores. Change scores between baseline and 12-month follow-up were computed for each outcome measure. Duration of symptoms was dichotomized into a "short" and "long" group at several cut-offs. An iterative mixed model analytic approach procedure was used to evaluate differences in change scores on the mJOA, Nurick, SF-36 MCS and PCS and NDI between duration groups in 1-month increments. Two models were constructed: 1) an unadjusted model between duration of symptoms and surgical outcome and 2) a model adjusting for significant independent covariates identified through stepwise regression analysis. Results: Our cohort consisted of 201 (57.43%) men and 149 (42.57%) women, with a mean age of 57.49 ± 11.77 years (range: 29–87 years). The mean duration of symptoms was 25.71 ± 36.68 months (range: 1–240 months). In unadjusted analysis, patients with a duration of symptoms shorter than 4 months had significantly better functional outcomes based on the mJOA ( p = 0.04) than patients with a longer duration of symptoms (>4 months). On average, patients with a shorter duration of symptom improved by 3.71 on the mJOA, whereas those with a duration 4 months or longer only exhibited a 2.96 mean gain. Twelve months was identified as the next important cut-off beyond which patients had a significantly worse outcomes on the mJOA; however, this difference was smaller. Following adjusted analysis, cut-offs of 4 and 12 months remained significant. Duration of symptoms was not associated with Nurick or SF-36 PCS or MCS in either the unadjusted or adjusted models. Conclusion: Patients who are operated on within 4 months of symptom presentation have better mJOA outcomes. It is recommended that patients with DCM are diagnosed in a timely fashion and referred early for surgical consultation. Our study does not support the traditional conservative "watchful waiting" approach to symptomatic patients with DCM.